Serum levels of copeptin predict adverse outcomes and improve risk prediction of TRISS and MGAP scores in patients with multiple trauma: A single-center prospective cohort study. Issue 2 (19th February 2023) - Hsein, Yenh-Chen; Wu, I-Ju; Tan, Jasmine; Huang, Sih-Shiang; Lu, Kuan-Ting; Su, Chin-Hua; Hsu, Wan-Ting; Chen, Shyr-Chyr; Lee, Chien-Chang
Abstract : As demonstrated in this prospective study, copeptin contributes to improved risk prediction when combined with TRISS or MGAP scores for polytrauma. Abstract : BACKGROUND: Multiple trauma deserves early prognostication and stratification. Copeptin, a precursor of vasopressin, is produced in response to stress. We examined the association between serum levels of copeptin and mortality risk in patients with multiple trauma. We aimed to also enhance the previously established Trauma-Related Injury Severity Score (TRISS) and Mechanism, GCS, Age, and Arterial Pressure (MGAP) score with the additional consideration of copeptin levels. METHODS: This single-center prospective cohort study enrolled patients who presented to the emergency department with potential major injuries. The serum levels of copeptin were measured, and the correlation to clinical severity in terms of 30-day mortality and requirement of intensive care management was analyzed. By combining copeptin levels with TRISS or MGAP, comparison between performance of the original models with the copeptin-enhanced models was performed via discrimination, calibration, and reclassification analyses. RESULTS: There was a significant increase in copeptin levels in patients who died within 30 days (median 644.4 pg/L, interquartile range [472.5, 785.9]) or were admitted to intensive care units (233.8 pg/L, [105.7, 366.4]), compared with those who survived (37.49 pg/L, [17.88, 77.68]). Adding the natural log of copeptin levels to the established TRISS and MGAP models improved the AUC of TRISS from 0.89 to 0.96, and that of MGAP from 0.82 to 0.95. Both calibrations as measured by Brier's scores and reclassification as measured by net reclassification improvement or integrated discrimination improvement demonstrated significant improvements. A Web-based calculator was built to generate predicted mortality rates of various models for convenient clinical use. CONCLUSION: Admission serum copeptin levels were correlated with clinical severity in multiple trauma. Coupling copeptin with preexisting trauma severity scores improved prediction accuracy. Copeptin shows promise as a novel biomarker for the prediction of trauma outcome. LEVEL OF EVIDENCE: Prognostic and Epidemiologic; Level III. Abstract :